PENGARUH EARNING PER SHARE, ROE, DER DAN BVS TERHADAP HARGA SAHAM PADA BANK PEMERINTAH YANG TERDAFTAR DI BURSA EFEK INDONESIA - Fitri Utamie Alex; Nyayu Khairani Putri; Nina Fitriana (JURNAL KOMPETITIF, 2022)
The purpose in this research is to explain the influence the effect of Earning Pershare, Return on Equity, Debt on Equity and Book Value Pershare on stock prices in government banks listed on the Indonesia Stock Exchange (BEI). The sample used in this study were 4 companies in the government banking sector in the 2014-2018 period. The sample collection technique in this study used the documentation method. The data analysis method in this study used panel data regression. The results showed that; Earning per share (EPS) has no effect on stock prices, Return on Assets (ROE) has a positive effect on stock prices, Debt to Equity (DER) affects stock prices in a negative direction and Book Value Equity (BVS) affects prices stocks in a negative direction. EPS, ROE, DER, and BVS have an effect on stock prices, with an effect of 90.55%, while the remaining 9.45% is the fact by other variables outside the research.Keywords : Earning Per Share (EPS); Return on Equity (ROE); Debt to Equity (DER); Book Value Equity (BVS) dan Stock Price